Stroke 1-2-0-3-6: rapid identification and timely action for stroke in China - Chen Chen; Ziwei Hou; Li Li; Ruiying Wang; Hong Liu; Hui Shen (Frontiers in Neurology)
In 2016, doctors in China proposed the Chinese version of FAST, called Stroke 120, to improve stroke identification and response in the Chinese population. And we modified Stroke 120 by adding “3” and “6” which aimed to reduce the prehospital delays and improve the prognosis of patients with stroke.